Nuclear corrosion modeling : the nature of crud - Castelli, Roy.; ScienceDirect eBooks (Burlington, MA : Elsevier Butterworth-Heinemann, 2009)
Corrosion in nuclear power plants cause reductions in efficiency and increases in deposit build-up on plant surfaces, making for expensive maintentance and potential radiological health hazards. This book guides studies to predict and minimize corrosion, thus making nuclear power safer and more cost effective. Too often, reliance on empirical models and on-site testing of existing plants makes study and prediction of corrosive effects in nuclear reactors into a pricey and lengthy process. Introducing the experimental procedures, set up, sample preparation and computer modeling suggested in this book will save precious time and resources in a field where the significant time and expense to get and keep plants on-line are two of the chief concerns preventing broader commercial viability.
Corrosion source -- Framing the vision and the general equation set -- Building block fluxes for the general equation set -- General equation set -- Framing the vision of the media equation set -- Media equation set -- Solution method -- Defining the input architecture for NOC -- Program architecture -- Pre- and postprocessing (the GUI interface) -- Design applications.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Nuclear reactors -- Corrosion; Nuclear reactors -- Corrosion -- Mathematical models; Corrosion and anti-corrosives.; Nuclear power plants; Corrosion and anti-corrosives.; Nuclear power plants; Nuclear reactors -- Corrosion; Electronic books